PENGARUH PROBIOTIK STRAIN Lactobacillus TERHADAP LAJU PERTUMBUHAN DAN EFISIENSI PAKAN LELE MASAMO (Clarias sp) TAHAP PENDEDERAN I DENGAN SISTEM BIOFLOK SEBAGAI SUMBER BIOLOGI - Lely Yuriana; Handoko Santoso; Agus Sutanto (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2017)
Provision of probiotics in feed or catfish culture media is an effort to increase the growth rate, improve the digestibility of feed and maintain the quality of the cultivation environment. This study aims to determine the effect of probiotic Lactobacillus strain on the growth rate and efficiency of feed utilization of catfish masamo stage I by using the biofloc system, knowing the best probiotic doses of Lactobacillus strain and preparing the research as a learning resource in the form of LKPD. The research design was using Completely Randomized Design (RAL) with 4 treatments and 5 replications. Treatment was a variation of probiotic dose of Lactobacillus strain consisting of P0 treatment (without probiotics), P1 (5 mg / kg of feed), P2 (10 mg / kg of feed) and P3 (15 mg / kg of feed). The results showed that probiotic Lactobacillus strain on feed affected the growth rate and feed efficiency level (EPP) of masamo fish significantly (P> 0.05). The best treatment was P3 with 15 mg / kg of probiotics which resulted in average growth rate of length, weight, daily, EPP of 1.43 cm each; 1.02 gr; 7.30% and 37.87%, whereas treatment without probiotics (P0) yielded 1.04 cm each; 0.93 gr; 6.65% and 34.48%. Research results can be developed as learning resources in the form of LKPD.